Quality assessment and evaluation of the aphrodisiac property and toxicity profile of a Ghanaian herbal male vitality booster - Paul K. Osei; Evelyn Asante-Kwatia; Bernard K. Turkson; Isaac K. Amponsah; Reinhard I. Nketia; Lord Gyimah; Abraham Y. Mensah (Elsevier, 2024)
Background: Mist Campa-T (MCT) is a mono-herbal formulation has gained popularity in Ghana for its acclaimed effectiveness in improving sexual function in men. Its main active ingredient is Thoningia sanguinea, a plant known for its aphrodisiac property in folk medicine. This research focused on investigating the aphrodisiac effect of (MCT) and its toxicological profile. Methods: The effect of MCT on sexual function was investigated by the mounting and mating frequency assays followed by serum testosterone and sperm analysis. The toxicological assessment was performed by the acute and sub-acute toxicity assays. Microbial load and elemental/heavy metal content analysis of the product was ascertained. Results: MCT (250, 500, 1000 mg/kg/day) exhibited significant (P ≤ 0.0001) increase in mounting and mating frequencies, in male rats. There was a significant (P ≤ 0.0001) rise in testosterone level for the MCT-treated rats. The LD50 of Mist Campa-T was found to be above 2000 mg/kg bodyweight. There was no significant variation (P > 0.05) in haematological indices as well as renal or hepatic enzymes in the treated groups compared to the untreated group after 28 days of treatment with MCT. There was a notable increase (P < 0.01) in haemoglobin level of rats treated with MCT. Elemental and heavy metal content as well as microbial load were all within the range of permissible limits. Phytochemical screening of MCT revealed the presence of saponins, alkaloids, triterpenoids, sterols, reducing sugars and tannins. Conclusions: The overall results of this study have proven that Mist Campa-T is fairly safe and possesses aphrodisiac effect possibly due to its ability to increase serum testosterone level.